Antinociceptive properties of 25‐methoxy hispidol A, a triterpinoid isolated from Poncirus trifoliata (Rutaceae) through inhibition of NF‐κB signalling in mice. (19th November 2018) - Khan, Ashrafullah; Ullah, Muhammad Zia; Afridi, Ruqayya; Rasheed, Hina; Khalid, Sidra; Ullah, Hadayat; Ali, Hussain; AlSharari, Shakir D.; Kim, Yeong Shik; Khan, Salman
Abstract : The 25‐methoxy hispidol A (25‐MHA) is a triterpenoid, isolated from the immature fruit of Poncirus trifoliata (Rutaceae). The pretreatment with 25‐MHA markedly ( p  < 0.001) attenuated the formalin‐induced biphasic responses as well as acetic acid‐induced writhing responses. The intraperitoneal administration of 25‐MHA significantly attenuated the mechanical hyperalgesia ( p  < 0.001) and allodynia ( p  < 0.05). Similarly, 25‐MHA also significantly attenuated ( p  < 0.001) complete Freund's adjuvant (CFA)‐induced paw edema in mice. The 25‐MHA treatment significantly attenuated the production of nuclear kappa B (NF‐κB) (p65 nuclear subunit). The cytokines are the important mediators of inflammation and pain; however, treatment with 25‐MHA exhibited significant inhibition ( p  < 0.001) on the mRNA expression levels of various inflammatory mediators. The 25‐MHA administration also significantly enhanced antioxidant enzymes ( p < 0.001) and inhibited the oxidative stress markers. The current study indicates that 25‐MHA significantly ( p  < 0.001) inhibited the nitric oxide (NO) in mice plasma. Similarly, the haematoxylin and eosin (H&E) staining shows that 25‐MHA administration significantly inhibited the inflammatory process in the mice paw tissue compared with the CFA‐treated group. The 25‐MHA treatment did not exhibited any toxicity on the liver, kidney, muscles strength, and motor co‐ordination in mice. The 25‐MHA was coadministered with the various drugs such as tramadol, piroxicam, and gabapentin to observe the synergistic effect.